Water physicochemical characterization and phytoplankton diversity of arid region in Meggarine Lake, Ouargla, Algeria (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Manamani R, Bensouilah M. 2023. Water physicochemical characterization and phytoplankton diversity of arid region in Meggarine Lake, Ouargla, Algeria. Biodiversitas 24: 1569-1579. The present study aims to examine the physicochemical parameters, e.g., temperature, dissolved oxygen, pH, conductivity, salinity, nitrites, nitrates, orthophosphates, suspended matter, and chlorophyll (a) content) of Meggarine Lake, located in the Saharian region (Ouargla). Also, to establish the relation with phytoplankton's seasonal dynamics and diversification. From November through May over four years (2016-2019), a spatial and spatiotemporal investigation of phytoplankton composition was conducted. The algae and water samples were collected, preserved, and analyzed from four different sites using standard methods. Canonical Correlation Analysis (CCA) was recorded to explain the correlation between phytoplankton and physicochemical parameters. The results revealed a link between these planktonic populations and their physicochemical properties. Observing the morphoanatomical characters of the phytoplankton genera collected in Meggarine Lake allowed us to identify 29 genera. Diatoms (15 genera), dinoflagellates (03 genera), and cyanobacteria (11 genera) were separated into three groups. The distribution of phytoplankton showed a very high algal density in 2018, with a total of 9,995 cells/L, followed by 2019 and 2017, where the total densities were 5,332 and 5,118 cells/L, respectively. A low total density value was recorded (3,157.067 cells/L) in 2016. The highest value of phytoplankton was noted during the spring season, with 19,778 cells/L. Statistical analyses showed different correlations between the physicochemical parameters and the spatiotemporal variation of algae.
Keywords: Bioindicators, environmental factors, Meggarine Lake, physicochemical characterization, phytoplankton diversity